Evaluation of Specific and Non-Specific Cellular Immune Responses in Amoebiasis Patients - N Arianpour; TM Mohapatra (Tehran University of Medical Sciences, 2004)
Specific and non- specific cellular immune responses were studied in 20 amoebiasis cases and 10 controls. All the study cases and controls were Indians living in Varanasi, India. Ten amoebic liver abscess cases were patients admitted to University hospital. Ten non-invasive intestinal amoebiasis cases constituted the second study group. Non-specific immune responses were studied using E-rosette technique. Specific cellular immune response was evaluated by measuring tritiated thymidine uptake by transformed lymphocytes using crude amoebic extract prepared from axenically grown Entamoeba histolytica NIH: 200 and two of its chromatographed fractions, i.e. fraction I (FI) & fraction II (FII) as well as a mitogen, i.e. Phyto Haemagglutinin-A (PHA). Results show those crude antigens followed by FI & FII are able to induce blastoid transformation of lymphocytes prepared from different cases. Moreover, it was shown that specific cellular immune response was greatly depressed in amoebic liver abscess cases (P<0.001). While the CPM (count per minute) of different groups on using PHA for stimulation did not vary significantly.